Survival probability, weibull characteristics, stress distribution, and fractographic analysis of polymer-infiltrated ceramic network restorations cemented on a chairside titanium base: An in vitro and in silico study - Tribst, João P.M. [UNESP]; Dal Piva, Amanda M.O. [UNESP]; Borges, Alexandre L.S. [UNESP]; Anami, Lilian C.; Kleverlaan, Cornelis J.; Bottino, Marco A. [UNESP] (MDPI, 2020)
Different techniques are available to manufacture polymer-infiltrated ceramic restorations cemented on a chairside titanium base. To compare the influence of these techniques in the mechanical response, 75 implant-supported crowns were divided in three groups: CME (crown cemented on a mesostructure), a two-piece prosthetic solution consisting of a crown and hybrid abutment; MC (monolithic crown), a one-piece prosthetic solution consisting of a crown; and MP (monolithic crown with perforation), a one-piece prosthetic solution consisting of a crown with a screw access hole. All specimens were stepwise fatigued (50 N in each 20,000 cycles until 1200 N and 350,000 cycles). The failed crowns were inspected under scanning electron microscopy. The finite element method was applied to analyze mechanical behavior under 300 N axial load. Log-Rank (p = 0.17) and Wilcoxon (p = 0.11) tests revealed similar survival probability at 300 and 900 N. Higher stress concentration was observed in the crowns' emergence profiles. The MP and CME techniques showed similar survival and can be applied to manufacture an implant-supported crown. In all groups, the stress concentration associated with fractographic analysis suggests that the region of the emergence profile should always be evaluated due to the high prevalence of failures in this area.
Keywords: Ceramics; Dental implant-abutment design; Dental implants; Dental materials; Finite element analysis; Material testing